Sequence Variation and Expression of the Gimap Gene Family in the BB Rat. (19th March 2009) - Rutledge, Elizabeth A.; Fuller, Jessica M.; Van Yserloo, Brian; Moralejo, Daniel H.; Ettinger, Ruth A.; Gaur, Prashant; Hoehna, Jana L.; Peterson, Morgan R.; Jensen, Richard; Kwitek, Anne E.; Lernmark, Åke
Abstract : Positional cloning of lymphopenia ( lyp ) in the BB rat revealed a frameshift mutation in Gimap5, a member of at least seven related GTPase Immune Associated Protein genes located on rat chromosome 4q24. Our aim was to clone and sequence the cDNA of the BB diabetes prone (DP) and diabetes resistant (DR) alleles of all seven Gimap genes in the congenic DR. lyp rat line with 2 Mb of BB DP DNA introgressed onto the DR genetic background. All (100%)DR . l y p / l y p rats are lymphopenic and develop type 1 diabetes (T1D) by 84 days of age whileDR . + / + rats remain T1D and lyp resistant. Among the seven Gimap genes, the Gimap5 frameshift mutation, a mutant allele that produces no protein, had the greatest impact on lymphopenia in theDR . l y p / l y p rat. Gimap4 and Gimap1 each had one amino acid substitution of unlikely significance for lymphopenia. Quantitative RT-PCR analysis showed a reduction in expression of all seven Gimap genes inDR . l y p / l y p spleen and mesenteric lymph nodes when compared toDR . + / + . Only four; Gimap1, Gimap4, Gimap5, and Gimap9 were reduced in thymus. Our data substantiates the Gimap5 frameshift mutation as the primary defect with only limited contributions to lymphopenia from the remaining Gimap genes.